Prevalence of snoring and craniofacial features in Malaysian children from hospital-based medical clinic population - Banabilh, Saeed; Asha'ari, Zamzil Amin; Hamid, Suzina (Springer-Verlag, 2008)
Snoring is considered as the most common clinical symptom of obstructive sleep apnea–hypopnea syndrome. However, many snoring studies were done in western population, and data from around Asia is scarce. Therefore, the purposes of this study were to determine the prevalence of snoring among Malaysian children from hospital-based medical clinic population setting and to compare the craniofacial features of children with and without snoring using cephalometric analysis. A crosssectional study among children aged 7–15 years were carried out in Hospital Kuala Terengganu. Sleep behavior questionnaire (Berlin questionnaire) was given to 500 children. The respondents were divided into snoring and non-snoring groups. Thirty children from each group were randomly selected to undergo a cephalometric X-ray. For each lateral cephalometric radiograph, 17 parameters consisting bony, soft tissue, and angular measurements were recorded using computer software VixWin2000. Independent t test was used to analyze the data. The results indicated that the whole questionnaire respondents were 317 (46 snoring and 271 non-snoring), hence, the prevalence of snoring in our survey population was 14.51%. The cephalometric X-ray showed that the snoring children manifested a significant different craniofacial features, such as narrow airway at the level of the soft palate and oropharynx (p<0.05), more inferiorly positioned hyoid bone (p<0.05), longer vertical airway length from posterior nasal spine to the base of epiglottis (p<0.05), more protruding maxilla, and anterior–posterior discrepancy of maxilla and mandible (p<0.05). In conclusion, our snorer children exhibit significant craniofacial differences compared to non-snorer groups.